Imaging organoids: a correlative light- and electron microscopy approach - Willemsen, Sam (Student Undergraduate Research E-journal!, 2019)
Organoids are important pharmacological and disease models. To better study organoids, existing approaches have to be adapted. Correlative microscopy approaches allow for a more holistic understanding of cellular events. While beneficial to study organoids, an effective correlative protocol for organoids has yet to be established. The current paper presents an initial correlative workflow for organoids. Two-photon light microscopy is applied to capture characteristics of organoids and co-cultured bacteria. Furthermore, 3D models and near-infrared branding are explored to guide the recovery of a region of interest for electron microscopy. Finally, different sample preparations are tested on compatibility with a correlative workflow.